2014
DOI: 10.1098/rsif.2013.1112
|View full text |Cite
|
Sign up to set email alerts
|

Complexity analysis of sleep and alterations with insomnia based on non-invasive techniques

Abstract: For the first time, fractal analysis techniques are implemented to study the correlations present in sleep actigraphy for individuals suffering from acute insomnia with comparisons made against healthy subjects. Analysis was carried out for 21 healthy individuals with no diagnosed sleep disorders and 26 subjects diagnosed with acute insomnia during night-time hours. Detrended fluctuation analysis was applied in order to look for 1/f-fluctuations indicative of high complexity. The aim is to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…The mean ± SD age at onset for BD in this sample was 22.8 ± 9.3 years; patients with comorbid disorders had an earlier age at onset of the disorder [16.1 ± 4.7 versus 24.8 ± 9.8 years for those without comorbid disorders; F = 4.14, p = 0.05], consistent with our previous results . Most of the patients in this sample were taking mood stabilizers; nine were receiving antidepressant treatment, and eight were taking antipsychotics (Table ). Sleep‐aid medications were prescribed for nine of the patients; women were prescribed sleep medications more often than men (χ 2 = 7.59, p < 0.005).…”
Section: Resultssupporting
confidence: 89%
“…The mean ± SD age at onset for BD in this sample was 22.8 ± 9.3 years; patients with comorbid disorders had an earlier age at onset of the disorder [16.1 ± 4.7 versus 24.8 ± 9.8 years for those without comorbid disorders; F = 4.14, p = 0.05], consistent with our previous results . Most of the patients in this sample were taking mood stabilizers; nine were receiving antidepressant treatment, and eight were taking antipsychotics (Table ). Sleep‐aid medications were prescribed for nine of the patients; women were prescribed sleep medications more often than men (χ 2 = 7.59, p < 0.005).…”
Section: Resultssupporting
confidence: 89%
“…In particular, actigraphy studies by Sun et al [15] indicated that the scaling exponent of the power law detected in temporal autocorrelation of activity significantly correlates with the severity of Parkinson's disease symptoms. Similarly, universal scaling laws have been found in locomotor activity periods of humans suffering from major depressive disorders [12] and individuals subject to sleep debt [24,25]. The disruption of the characteristic universality classes of such laws has been further addressed by Proekt et al [7] in studies on dynamics of rest and activity fluctuations in light and dark phases of the circadian cycle.…”
Section: Experiment: Actigraphy Recordingsmentioning
confidence: 94%
“…While such summary measures allow for hypothesis testing using classic statistical methods [14,[21][22][23], large amounts of relevant information are disclosed in those complex data when more advanced tools of quantification (cf. Section 3), like fractal analysis, are applied [11,13,15,17,24,25]. In particular, actigraphy studies by Sun et al [15] indicated that the scaling exponent of the power law detected in temporal autocorrelation of activity significantly correlates with the severity of Parkinson's disease symptoms.…”
Section: Experiment: Actigraphy Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…All time series have a length of N ¼ 20160 data points (corresponding to 7 Â 24 h) (data from the public database of Ref. [43]).…”
Section: Introductionmentioning
confidence: 99%